2011
DOI: 10.1063/1.3573807
|View full text |Cite
|
Sign up to set email alerts
|

Plasma confinement by hemispherical cavity in laser-induced breakdown spectroscopy

Abstract: An aluminum hemispherical cavity ͑diameter: 11.1 mm͒ was used to confine plasmas produced by a KrF excimer laser in air from a steel target with a low concentration manganese in laser-induced breakdown spectroscopy. A significant enhancement ͑factor Ͼ12͒ in the emission intensity of Mn lines was observed at a laser fluence of 7.8 J / cm 2 when the plasma was confined by the hemispherical cavity, leading to an increase in plasma temperature about 3600 K. The maximum emission enhancement increased with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…Popov et al reported the confinement effect of plasmas created in a small capped cylindrical chamber whose size was 4 mm by 4 mm, improved the limit of detection (LOD) by two to five times for different elements [24,25]. Our previous research also showed the enhancement of plasmas confined with an aluminum hemispherical cavity, resulting in an enhancement factor of 12 for Mn lines in a substrate with a low Mn concentration [26,27]. Wang et al fabricated a polytetrafluoroethylene (PTFE) plate of 1.5 mm thick with a diameter of 3 mm to regularize coal plasma.…”
Section: Introductionmentioning
confidence: 92%
“…Popov et al reported the confinement effect of plasmas created in a small capped cylindrical chamber whose size was 4 mm by 4 mm, improved the limit of detection (LOD) by two to five times for different elements [24,25]. Our previous research also showed the enhancement of plasmas confined with an aluminum hemispherical cavity, resulting in an enhancement factor of 12 for Mn lines in a substrate with a low Mn concentration [26,27]. Wang et al fabricated a polytetrafluoroethylene (PTFE) plate of 1.5 mm thick with a diameter of 3 mm to regularize coal plasma.…”
Section: Introductionmentioning
confidence: 92%
“…In the past, researchers only studied the plasma confinement effects using either spatial or magnetic confinement. For instance, our previous research [23] studied the enhancement of plasmas confined with an aluminum hemispherical cavity, resulting in an enhancement factor of 12 for Mn lines of low-concentration Mn element. Rai et al [24] have studied the magnetic field confinement effect in air with a homemade magnetic device, achieving a maximum enhancement factor of 2 for metal alloy samples.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to improve the sensitivity of LIBS, such as, dualpulse excitation [8][9][10], spatial or magnetic confinement [11][12][13][14], microwave-assisted LIBS [15], and laser ablation combined with fast pulse discharge [16]. Generation of hightemperature and low-density plasmas in LIBS to improve the spectral resolution has also been achieved by introducing a second laser pulse to re-ablate the laser-induced particles with delays up to milliseconds [17].…”
Section: Introductionmentioning
confidence: 99%